"Social Networkout": Connecting Social Features of Wearable Fitness Trackers with Physical Exercise. Issue 12 (2nd December 2017) - Zhu, Yaguang; Dailey, Stephanie L; Kreitzberg, Daniel; Bernhardt, Jay
Abstract : Despite widespread understanding of the benefits of physical activity, many adults in the United States do not meet recommended exercise guidelines. Burgeoning technologies, including wearable fitness trackers (e.g., Fitbit, Apple watch), bring new opportunities to influence physical activity by encouraging users to track and share physical activity data and compete against their peers. However, research has not explored the social processes that mediate the relationship between the use of wearable fitness trackers and intention to exercise. In this study, we applied the Theory of Planned Behavior (Ajzen, 1991) to explore the effects of two communicative features of wearable fitness devices—social sharing and social competing—on individuals' intention to exercise. Drawing upon surveys from 238 wearable fitness tracker users, we found that the relationship between the two communication features (social sharing and competing) and exercise intention was mediated by attitudes, subjective norms, and perceived behavioral control. The results suggest that the ways in which exercise data are shared significantly influence the exercise intentions, and these intentions are mediated by individuals' evaluation of exercise, belief about important others' approval of exercise, and perceived control upon exercise.